The hermetic Deleuze : philosophy and spiritual ordeal - Ramey, Joshua Alan, 1975- (New slant., 2012)
In this book, Joshua Ramey examines the extent to which Gilles Deleuze's ethics, metaphysics, and politics were informed by, and can only be fully understood through, this hermetic tradition.